Catalytic ozonation of humic acid in water with modified activated carbon: Enhancement and restoration of the activity of an activated carbon catalyst. (1st May 2019) - Feng, Jing; Xing, Bo; Chen, Honglin
Abstract: Catalytic ozonation of organic compounds in water is an important research area for addressing the current pollution crisis. The objective of the present study was to find a modification method for enhancing and restoring the activity of the activated carbon (AC) catalyst applied in the catalytic ozonation of the humic acid (HA) aquatic contaminant. A three-step treatment consisting of an initial thermal treatment, oxidation treatment, and further thermal treatment increased the amount of surface hydroxyl groups (COH) of AC while reducing the amounts of other surface groups, such as basic, carboxyl, lactone, and carbonyl groups. The obtained ACN2 O2 N2 shows better catalytic performance for HA ozonation than virgin AC, and the COD removal improved from 71% to 96% after reacting for 10 min. This modification method could also restore the catalytic activity of used ACN2 O2 N2, as the COD removal improved from 74% to 97% after reacting 10 min. The apparent first-order rate constant (kapp ) was obtained by fitting the evolution of TOC. The regression analyses of the relationships between the kapp and the surface chemical properties, textural properties, and degree of AC graphitization showed that the increase in the amount of COH was the main factor driving the enhancement and restoration of the AC catalyst activity. Graphical abstract: Image 101 Highlights: Here studied the activity and stability of activated carbon in catalytic ozonation. Surface chemical properties impact the catalytic activity of activated carbon. A methodology was developed to changed surface properties of activated carbon.